A Systemic Approach For a Sustainable Coffee Production in Indonesia - Muhammad Ibnu (SOCA: Jurnal Sosial Ekonomi Pertanian, 2022)
Standard and certification are related to the sustainable development paradigm that views agriculture as a system. However, studies on standard and certification, especially in Indonesia, rarely evaluate it as a systemic approach to agricultural development. This study aimed to analyze the parallels of the standard and certification with the premise of The Theory of Change–can contextually provide incentives for a systemic approach to sustainable coffee production in Indonesia and to examine the proper systemic approach for a sustainable system of the Indonesian coffee production. We conducted a literature review to address the study aims. Empirical and theoretical approach studies included in the review process. Findings revealed that standard and certification did not provide adequate incentives for systemic and sustainable coffee production in Indonesia. Thus, a combination of five building blocks as a conceptual systemic approach is required to encourage sustainable coffee production. These building blocks are composed of enabling environment, production and market characteristics, the availability of alternative livelihoods, and the level of competition among producers.